Can Parents' Socioeconomic Determinants Increase Students' Interest in Continuing Education in the Future? - Dadang Saepuloh; Imam Sudarmaji; Andi Yustira Lestari Wahab; Deis Khoerunisa (Journal of Innovation in Educational and Cultural Research, 2024)
Fostering students' interest in continuing their education to higher education is critical to improving the quality of human resources. School involvement and the parent role are significant in fostering students' concern to continue their education to college. Therefore, this study examines the socioeconomic influence of parents, social environment, and self-actualization on students' interest in continuing studies. The researchers have collected data using incidental sampling techniques on 404 high school students. Instruments distributed to respondents have been tested for validity and reliability. Multiple regression was used for data analysis. The study results find that parents' socioeconomic, social environment and self-actualization significantly affect students' interest in continuing their studies. So, to increase students' attractiveness, the school as a social environment and parents who work together have a vital role in facilitating students by holding outreach activities and encouraging them to continue their education in tertiary institutions. This study provides academic insight into pedagogical research and educational development in adolescents. These findings contribute to future researchers and policymakers focused on increasing interest in continuing education in higher education.